Kedudukan Hukum Perjanjian Jual Beli Atas Dasar Utang Piutang (Studi Putusan Pengadilan Negeri Denpasar Nomor 10/Pdt.G/2019/PN Dps) - Aristiono Hamdani; Miftakhul Huda (Jurnal Interpretasi Hukum, 2024)
A notary holds significant responsibility for every action related to the creation of an authentic deed. This responsibility extends not only during the creation of the deed but also for as long as the deed is used by the involved parties. The notary is accountable for the authenticity and accuracy of the deed's content to ensure no harm is caused to any party. One example is a debt agreement that later transformed into a sale and purchase agreement in the Denpasar District Court Decision No. 10/Pdt.G/2019/PN Dps. Based on this, the study addresses two main questions: (1) What is the legal strength of the sale and purchase agreement as evidence? and (2) What is the ratio decidendi concerning the evidentiary strength of the sale and purchase agreement in the Supreme Court Decision No. 2053K/PDT/2019? This study employs a normative method, specifically a juridical analysis of applicable legal norms. The purpose is to identify the factors leading to the lawsuit in the Denpasar District Court and analyze the judges' considerations regarding the legal status of a sale and purchase agreement based on debt. The findings indicate that the Supreme Court Decision No. 2053K/PDT/2019 is accurate, as it considers the principles of immediate payment and transparency, as well as the validity requirements of the agreement. The defendant did not acknowledge the sale and purchase agreement, but rather a debt. Therefore, the lawsuit should be dismissed.